A case of primary infertility and a patient with ventriculoperitoneal shunt. Issue 12 (17th December 2022) - Eliasi, Elior; Cohen, Adiel; Wasser, Oren; Oelsner, Gabriel
Abstract: Ventriculoperitoneal (VP) shunts are the main treatment modality for patients with hydrocephalus. The complications arising in patients with VP shunts are well documented. We present a case of infertility in a patient with a long-standing VP shunt. Her infertility is thought to be the result of pelvic adhesions due to factors related to the distal end of her VP shunt. A 22-year-old female with a 1-year history of infertility was referred due to bilateral hydrosalpinges. Diagnostic laparoscopy revealed multiple adhesions surrounding the distal end of the fallopian tubes. The distal portion of a VP shunt, which was placed over the course of her childhood, was found to be grossly inflamed and densely adherent to the pelvic viscera. VP shunts may produce abdominal adhesions and can cause mechanical infertility.